2022
DOI: 10.1002/anie.202201865
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Insulator‐Semiconductor Anodes for Ultrastable and Site‐Selective Upconversion Photoinduced Electrochemiluminescence

Abstract: Photoinduced electrochemiluminescence (PECL) allows the electrochemically assisted conversion of low-energy photons into high-energy photons at an electrode surface. This concept is expected to have important implications, however, it is dramatically limited by the stability of the surface, impeding future developments. Here, a series of metal-insulator-semiconductor (MIS) junctions, using photoactive n-type Si (n-Si) as a light absorber covered by a few-nanometerthick protective SiO x /metal (SiO x /M, with M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(67 citation statements)
references
References 62 publications
(39 reference statements)
4
63
0
Order By: Relevance
“…48 As seen in Figure 2e, n-Si BPEs constantly illuminated and subjected to an external potential of 1.6 V can generate PECL for 22 h because of the protection provided by the SiO x /Ir coating. 21 To further elucidate this behavior, simulations were performed for the n-Si-based BPE by using the parameters obtained with the three-electrodes setup (Table S1 and Figure 1) and treating the two phases in contact with Si (electrolyte at the δ − pole and Ir at the δ + pole) as Schottky contacts having a difference in Fermi levels controlled by the external bias. The results, discussed in the Supporting Information (section 2), allowed determining the band diagram of the BPE (Figure S2) and confirmed that the BPE presents rectification, photoactivity, and decreased onset bias because of photovoltage generation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…48 As seen in Figure 2e, n-Si BPEs constantly illuminated and subjected to an external potential of 1.6 V can generate PECL for 22 h because of the protection provided by the SiO x /Ir coating. 21 To further elucidate this behavior, simulations were performed for the n-Si-based BPE by using the parameters obtained with the three-electrodes setup (Table S1 and Figure 1) and treating the two phases in contact with Si (electrolyte at the δ − pole and Ir at the δ + pole) as Schottky contacts having a difference in Fermi levels controlled by the external bias. The results, discussed in the Supporting Information (section 2), allowed determining the band diagram of the BPE (Figure S2) and confirmed that the BPE presents rectification, photoactivity, and decreased onset bias because of photovoltage generation.…”
mentioning
confidence: 99%
“…Interestingly, the photons produced by ECL can be used to trigger photoelectrochemistry at SCs. , Conversely, ECL can be triggered at the surface of an illuminated SC photoelectrode via a mechanism termed photoinduced ECL (PECL) . Taking advantage of the absorption properties of the different SC materials and emission properties of ECL luminophores, PECL can be employed to convert light in different ways. For instance, it can be used to perform anti-Stokes conversion of IR into visible radiation at low applied potentials by using a narrow bandgap photoelectrode (such as Si) and an ECL system emitting visible light. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 However, progress made on photoelectrode materials and SC protection strategies recently allowed the promotion of considerable progress in PECL. For instance, the infrared (IR)-to-visible conversion of photons by anti-Stokes PECL was demonstrated with [Ru(bpy) 3 ] 2+ /TPrA, 19,20 and the luminol/H 2 O 2 systems at n-type Si (n-Si)-based photoanodes. 21 In this approach, Si is particularly prone to anodic corrosion processes and requires the use of protection strategies, i.e., its coverage by an oxide and a metal thin film 19,20 or the covalent grafting of an organic monolayer.…”
mentioning
confidence: 99%
“…For instance, the infrared (IR)-to-visible conversion of photons by anti-Stokes PECL was demonstrated with [Ru(bpy) 3 ] 2+ /TPrA, 19,20 and the luminol/H 2 O 2 systems at n-type Si (n-Si)-based photoanodes. 21 In this approach, Si is particularly prone to anodic corrosion processes and requires the use of protection strategies, i.e., its coverage by an oxide and a metal thin film 19,20 or the covalent grafting of an organic monolayer. 21 An anodic ECL system was also investigated using more stable oxide-based n-type SC photoanodes (BiVO 4 or a-Fe 2 O 3 ), but the higher band gap value of such materials allowed only Stokes-type PECL conversion.…”
mentioning
confidence: 99%